Bankruptcy Prediction Analysis Using the Altman Z-Score Method at PT Aneka Tambang (Persero) Tbk - Iis Fitriani; Puji Muniarty (Yayasan Ilomata, 2020)
This study aims to determine the prediction of bankruptcy in Aneka Tambang (Persero) Tbk for the period 2011 to 2018. Z-score is the independent variable (X) measuring by five ratios: working capital to total assets, retained earnings to total assets, earnings before interest and tax to total assets, the market value of equity to total liabilities, and sales to total assets. The background of this research is the government's ban on the export of raw minerals, which resulted in Aneka Tambang (Persero) Tbk no longer making overseas sales of nickel ore, which made the company's profit decline. This research method uses descriptive research with a quantitative approach, the source of the data used is secondary data based on financial reports published on the Indonesia Stock Exchange and the official website www.antam.com. The population used is the financial statement data for ten years, namely from 2009 to 2018, while the sample using for eight years, namely from 2011 to 2018. The data collection technique carried out using documentation and literature study techniques. Data analysis techniques were carried out by discriminant analysis using the Altman Z-Score method and one sample t-test analysis. The Altman Z-Score uses five variables that represent liquidity ratios X1, profitability ratios X2 and X3, and activity ratios X4, and X5. The formula Z-Score Z = 0.717 X1 + 0.847 X2 + 3.107 X3 + 0.420 X4 + 0.998 X5. With criteria, Z> 2.99 categorized as a good company. Z between 1.23 to 2.99 categorized as a company in the grey area or area of ​​financial difficulty. Z <1.23 is categorized as a potentially bankrupt company.